Usulan Strategi Penetapan Value Based Pricing pada UMKM: Studi pada UMKM Amoira - Dinanti, Maharani Putri (Jurnal Riset Bisnis dan Investasi, 2023)
way possible. Interviews with purposive sample determination and observation were conducted using the descriptive qualitative approach. The data was analyzed using a variety of approaches, including the Sustainable Competitive Advantage (SCA) framework, the VRIO framework, and TOWS analysis Then the researcher conducted a content analysis to propose a pricing strategy. The recommended proposal is a pricing strategy with a Value-Based Pricing approach. Keywords: Pricing Strategy, Value-Based Pricing